Genomic insights into disease vectors: Divergent evolution of mosquitoes, tsetse flies, sand flies and kissing bugs - Lifeng Du; Jingwen Wang (Decoding Infection and Transmission, 2025)
Vector-borne diseases pose major global health challenges, with mosquitoes, tsetse flies, and sand flies serving as key insect vectors. This review explores the genomic basis of hematophagy, reproduction, and vector competence across these species. Comparative analyses reveal significant differences in genome size, transposable element content, chemosensory gene repertoires, immune pathways, and symbiotic associations. Mosquitoes possess large, transposable elements (TEs)-rich genomes and expanded antiviral gene families, supporting broad arbovirus transmission. Tsetse flies exhibit compact genomes with viviparous adaptations and obligate symbiosis aiding trypanosome transmission. Sand flies display streamlined genomes with species-specific immune responses and salivary factors that facilitate Leishmania infection. Kissing bugs, with moderate fecundity, lineage-specific immune adaptations, transmit Trypanosoma cruzi across species. These findings highlight how genomic architecture shapes vectorial capacity, offering insights for targeted disease control.